2022
DOI: 10.3389/fpubh.2022.1054765
|View full text |Cite
|
Sign up to set email alerts
|

Trends of late HIV presentation and advance HIV disease among newly diagnosed HIV cases in Jiangsu, China: A serial cross-sectional study from 2008 to 2020

Abstract: BackgroundThis study aimed to assess the trends and determine the factors associated with late presentation (LP) and advanced HIV disease (AHD) among newly diagnosed people living with HIV (PLWH) from 2008 to 2020 in Jiangsu, China.MethodsNewly diagnosed PLWH registered in the HIV surveillance system from 2008 to 2020 were included. Multivariable logistic regression models were used to analyze the factors associated with LP and AHD. The LP and AHD trends were assessed using Joint-point analysis.ResultsOf 37,25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Other studies performed during a similar timeframe (2017 to 2020, 2019 to 2020 and 2015 to 2020) also revealed that male and older patients are at greater risk of late HIV presentation [ 23 , 24 , 25 ]. Additionally, other LP risk factors, including bisexual transmission, heterosexual transmission, being married, SSA origin, tuberculosis or hepatitis C virus coinfection, lower socioeconomic status and the fear of stigma, have been reported in various studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The discrepancies observed among those studies highlight the importance of identifying populations at risk of late presentation and developing specific guidelines according to the region.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies performed during a similar timeframe (2017 to 2020, 2019 to 2020 and 2015 to 2020) also revealed that male and older patients are at greater risk of late HIV presentation [ 23 , 24 , 25 ]. Additionally, other LP risk factors, including bisexual transmission, heterosexual transmission, being married, SSA origin, tuberculosis or hepatitis C virus coinfection, lower socioeconomic status and the fear of stigma, have been reported in various studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The discrepancies observed among those studies highlight the importance of identifying populations at risk of late presentation and developing specific guidelines according to the region.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding health-seeking and health maintenance behaviors is pivotal for the control and treatment of HIV. A significant number of patients show delayed healthcare-seeking patterns, leading to a higher risk of community transmission (Shi et al, 2020). The current healthcare policies, infrastructure, and socio-demographic profile of HIV patients contribute to the complexity of improving health-seeking behaviors and adherence to treatment (Chirambo et al, 2019).…”
Section: Background Of Health-seeking Behavior and Challenges In Hiv ...mentioning
confidence: 99%
“…7 Published data showed varying differences in changes in the proportion of advanced HIV disease among people presenting for care at clinics in South Africa with some little or no change 8 , 9 while others reported substantial decline over the years. 10 - 12 A larger proportion of people with advanced HIV are ART experienced 2 suggesting that the majority of these seek care late when their health has already deteriorated although the proportion of late presenters and those initiating ART with advanced HIV is slowly decreasing 11 , 13 with mixed results in others. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 10 - 12 A larger proportion of people with advanced HIV are ART experienced 2 suggesting that the majority of these seek care late when their health has already deteriorated although the proportion of late presenters and those initiating ART with advanced HIV is slowly decreasing 11 , 13 with mixed results in others. 12 …”
Section: Introductionmentioning
confidence: 99%